2012
DOI: 10.1159/000336568
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Systemic Redox States in Patients Carrying the MELAS A3243G Mutation in Mitochondrial DNA

Abstract: Background/Aims: To clarify the change of systemic redox states in patients carrying the A3243G mutation in mitochondrial DNA (A3243G), we evaluated oxidative stress and antioxidant activity in the serum of patients. Methods: Oxidative stress and antioxidant activity in the serum samples obtained from 14 patients carrying A3243G and from 34 healthy controls were analyzed using the diacron-reactive oxygen metabolites (d-ROMs) and biological antioxidant potential (BAP) tests, respectively. Results: The mean d-RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Similar phenomena have also been found in patients with mitochondrial encephalomyopathy and lactic acidosis with stroke-like episodes (MELAS) [66] and Leber's hereditary optic neuropathy (LHON) [67] .…”
Section: Mitochondrial Dysfunctionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar phenomena have also been found in patients with mitochondrial encephalomyopathy and lactic acidosis with stroke-like episodes (MELAS) [66] and Leber's hereditary optic neuropathy (LHON) [67] .…”
Section: Mitochondrial Dysfunctionsupporting
confidence: 68%
“…Studies have revealed a causal relationship between mtDNA mutations and ROS production in the affected tissues of patients with mitochondrial diseases, when the mutation load of mtDNA reaches a threshold [63,64] . For example, skin fibroblasts isolated from patients with myoclonic epilepsy with red ragged fi bers (MERRF) show enhancement of intracellular hydrogen peroxide levels and oxidative damage, and an imbalance of gene expression of antioxidant enzymes [65] .Similar phenomena have also been found in patients with mitochondrial encephalomyopathy and lactic acidosis with stroke-like episodes (MELAS) [66] and Leber's hereditary optic neuropathy (LHON) [67] . …”
mentioning
confidence: 80%
“…A recent study in 14 Japanese MELAS patients detected evidence for peripheral redox imbalance by measuring diacron-reactive oxygen metabolites and biological antioxidant potential testing. Although mutant load was not reported, the patients studied had more severe clinical symptoms than our cohort [40]. Further studies in MELAS patients with more significant clinical disease and higher levels of mutant load in peripheral blood would be needed in order to study the potential relationship between mutant load and redox status in more detail.…”
Section: Discussionmentioning
confidence: 83%
“…Cytoplasmic hybrids (cybrids) harboring the A8344G mutation exhibit decreased efficiency of ATP synthesis in mitochondria and become more sensitive to extrinsic oxidative stress such as hydrogen peroxide and UV irradiation [2426] and the skin fibroblasts from MERRF patients demonstrate higher intracellular hydrogen peroxide levels and increased oxidative damage to the mitochondrial proteins containing iron–sulfur along with imbalance in the gene expression of antioxidant enzymes [27]. Human MELAS (mitochondrial encephalomyopathy and lactic acidosis with stroke-like episodes) patients carrying the A3243G mutation of mtDNA demonstrated increased oxidative stress systemically [28]. Leber’s hereditary optic neuropathy (LHON) results from one of three point mutations in mtDNA coding for complex I components and LHON cybrids have increased superoxide production compared to wild-type cells [29].…”
Section: Mitochondrial Dna and Oxidative Stressmentioning
confidence: 99%